SEJARAH BANGUNAN BENTENG BELANDA DI DESA BENTENG HULU KECAMATAN MEMPURA KABUPATEN SIAK - Nurlina Nurlina; Kamaruddin Oemar; Asril Asril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The term "fortress" reminds us of a context of defense and warfare, especially in the past. The castle belongs to a historic building because it reminds us of the Indonesian people's struggle against the colonials before independence. Fortresses in Indonesia are generally built during the Dutch colonial period. One of the fortress that still stands today is Dutch Fortress in Benteng Hulu Village, Mempura Subdistrict, Siak District. The fort is estimated to stand around the 1800s or the late 18th century. This fort is a complex of buildings that formerly served as a refuge and defense for the Dutch soldiers. In this fortress there are various buildings that among others serve as a prison, dormitory, office, arsenal, and others. The architecture of this Dutch fortress is European, with small rooms for weapons storage, prison space, meeting rooms and office space. Nowadays, this fortress is left untouched without proper use, therefore now the fort is much damaged and some even collapsed. Government efforts are needed to revive this historic building, so that later can be used as one of the Heritage Buildings of the Netherlands in Indonesia generally and in Siak in particular.Keywords: History, Building, Fortress, Netherlands, Benteng Hulu